Social factors affecting reconstruction of communities destabilized by war - Ajduković, Dean (Array, 2004)
Implications from several studies looking into the role of social context informed by organized violence that destabilized the societies and communities during the war in Croatia and Bosnia Herzegovina were presented. Our retrospective study of feelings of trust and betrayal by the close neighbours and life-long friends in the city of Vukovar (Ajdukovic and Corkalo, 2003) has clearly identified the interpersonal process that lead to loss of mutual trust, disruption of norms and decreasing quality and efficiency in close social transactions. In the study, 61 adults were interviewed about circumstances, experiences and consequences of separation in 1991 of close friends of Croat and Serb ethnic background in the conflicted city of Vukovar in which worst atrocities were committed. The increasing feelings of helplessness, fear and lack of full understanding of what was going on were the major factors that were identified as setting the stage for the break up of close relations. The crucial moment that made many of our respondents feel betrayed and broke off the friendships was their belief that their life-long friends had the information about what was going to happen, but failed to share it. Even in retrospect, after 12 years they were convinced that their friends withheld information that could mean life and death for them and their family, and left the city without telling them goodbye. Respondents from the other group never said that they withheld any information from their friends, and often described the dramatic circumstances under which they have urgently left the city. The recovery should be considered with the view on the present context which may include strong ethnic and other divisions, such as: tensions among former refugees and the local population, between those that became enormously rich during the war and those who became poor at the same time. The old social norms are gone and new ones are embraced by some, but then not by all members of such communities. For instance, the residents of the region of East Slavonia in Croatia (that has been severely affected by the war and atrocities) agree that before 1991, the relations among ethnic groups used to be very close, and that ethnicity of neighbors, colleagues at work or friends was of no relevance (Ajdukovic and Corkalo, in press). This social norm has drastically changed and the ethnic makeup became the key social marker in interpersonal relationships. The practice of Serbian and Croatian children attending separate schools has never been seen before. Such high level of community divide is true for sports, arts, and culture. Distrust, feeling of personal insecurity, and almost exclusive connection to one’ s own ethnic group is emphasized by the fact that most of the public places (coffee shops, restaurants) are either “ Croatian” or “ Serbian” . Members of an ethnic group do not look approvingly upon those who maintain even superficial contacts with persons belonging to the ethnic outgroup. A very important aspect of social context that can help the traumatized individuals and community heal is the perception of justice and accountability for crimes committed during violence. The expectation is that the individuals who are guilty of committing violence, criminal acts or atrocities, should be brought to justice. For example, the International Criminal Tribunal for Former Yugoslavia (ICTY) was established to investigate and prosecute war criminals in that region of Europe. The assumption is that if the truth about who did what in the past becomes known, people who were terrorized can begin to heal. At the social and community level this implies that a full accounting of crimes would facilitate reconciliation between former adversaries. In an extensive survey of a representative sample of 1642 residents from three ethnic groups living in three ethnically divided cities in Croatia (Vukovar) and Bosnia and Herzegovina (Mostar and Prijedor), among other issues, we have studied attitudes towards the International Criminal Tribunal for the Former Yugoslavia (ICTY) and war crimes (Biro, Ajdukovic, Corkalo, Djipa, Milin and Weinstenin, in press). How the international criminal trials are viewed very much depended on the group and study site. Bosniaks, who are seen by themselves and by the international community as principal victims of the wars, held positive while the other groups held negative attitudes towards the ICTY. At the time of the survey, other groups felt that the members of their ethnic group were unfairly singled out for show trials. Two years later, during the resurvey, these attitudes have changed – in the meantime, the Tribunal has indicted several high-ranking Bosnian military officers. Given the negative perception of the Tribunal, its role in contributing to reconciliation is evidently problematic. At the same time, the participants strongly felt that punishing war criminals from all sides was important for them personally and for the reconciliation. This apparently contradictory findings were easily explained by respondents who reported that they did not see the Tribunal as contributing to the reconciliation in their community. They felt that The Hague trials were far removed from their reality. They were discouraged as they insisted that perpetrators who have terrorized them lived freely in their community and that, of course, they will never be tried in The Hague. For them the Tribunal was a more or less irrelevant mechanism for delivery of justice that they were primarily interested in. Exposure to war trauma by itself was not predictive of reconciliation, but its association with negative experiences with other ethnic group, feeling discriminated and unsafe predicted resistance to reconciliation process. The key process that may be conductive to recovery from individual and collective traumatization and losses at the community level is the social reconstruction. The logic model combining possibly three different components leading to the social reconstruction was presented.